2017
DOI: 10.18632/oncotarget.22452
|View full text |Cite
|
Sign up to set email alerts
|

FTY-720 induces apoptosis in neuroblastoma via multiple signaling pathways

Abstract: Neuroblastoma (NB) is the most common extra-cranial pediatric solid tumor. High-risk NB is difficult to treat due to the lack of response to current therapies and aggressive disease progression. Despite novel drugs, alternative treatments and multi-modal treatments, finding an effective treatment strategy for these patients continues to be a major challenge. The current study focuses on examining the effects of FTY-720 or fingolimod, a drug that is FDA-approved for refractory multiple sclerosis, in NB. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Neuroblastoma (Nbl) is an embryonal tumour, originating from progenitor cells of the sympathetic nervous system, and is the most common extra-cranial solid tumour of childhood [1][2][3] . Nbl accounts for 7% of malignancies from birth to 14-y of age 4 and 12% of cancer deaths in children.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma (Nbl) is an embryonal tumour, originating from progenitor cells of the sympathetic nervous system, and is the most common extra-cranial solid tumour of childhood [1][2][3] . Nbl accounts for 7% of malignancies from birth to 14-y of age 4 and 12% of cancer deaths in children.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may not only be associated with the neuroprotective benefits of this drug 40 but also, its therapeutic effects in ischemia, excitotoxicity and memory recovery 4143 . Nevertheless, this drug could also negatively affect neurons, inducing apoptosis by altering calcium signalling and mitochondrial membrane potentials, effects that could be useful to sensitize neuroblastoma cells to anti-.neoplastic drugs 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, more evidence appeared in recent years suggesting that this compound accumulates in cells of the CNS, modulating the activity of neurons and astrocytes 14,15 , potentially making it suitable to treat a variety of neurological syndromes like ischemia, stroke and neurodegeneration 1618 . Furthermore, this drug has been also proposed for the treatment of neuronal cancers given its potential to induce the death of neuroblastoma cells 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms have been proposed for the effects of FTY720, including activation of PP2A [21] , [22] , generation of reactive oxygen species [44] , [45] , [46] , and inhibition of sphingosine kinase 1 (SphK1) [47] , [48] . Li and others showed that FTY720 inhibited sphingosine kinase 2 in neuroblastoma [49] , and Lange et al studied the effects on calcium channel signaling in neuroblastoma [50] , but neither group explored whether PP2A activation was involved [49] , [50] . In the current study, we found that FTY720 treatment significantly increased PP2A activity in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%